Questions of Linguistic-Ethnic Identity of the Autochthonous Georgians of Lazeti (the Laz) - Putkaradze, Tariel; Tandilava, Iasha; Labadze, Mikheil (Actual Problems of Kartvelology, 2012)
The Laz (Chanas) are one of the oldest and most powerful Georgian communities, which have played a leading role in the history of the Georgian state since ancient times. Most of the Laz are currently outside the borders of the Georgian state, but through their language, history, and culture, they constitute an integral part of the Georgian nation.